Uji Daya Hambat Fraksi Rumput Laut Merah Kappaphycus sp. terhadap Pertumbuhan Bakteri Staphylococcus aureus - Sufiah Asri Mulyawati; Yusmiati Yusmiati; Amiruddin Eso (Halu Oleo University, 2016)
Background:Staphylococcus aureus is gram positive bacteria can cause skin infections, pericarditis, osteomyelitis, septic arthritis, endocarditis and toxic shock syndrome. S. aureus common infection cause and found massively to be resistant to some antibiotics. Kappaphycus sp. is one type of red seaweed that has an bioactive compounds as antibacterial activity. Research Purposes:The purpose of this research determine the fraction of red seaweed Kappaphycus sp. to inhibition the growth of bacteria staphylococcus aureusResearch Methods:this research used experimental of design post test control only. Samples were obtained from the sub Tononggeu, Abeli. Inhibition test using disc diffusion method of various types of concentrations of fractions. Minimum inhibitory concentration (MIC) is determined by the lowest concentration that could inhibit the growth of bacteria. Positive control cefadroxil and negative control DMSO 10%. Research result:The result of this research shown that the fraction of n-hexane and ethyl acetate red seaweed Kappaphycus sp. has activity against bacterial growth Staphylococcus aureus seen with the clear zone. Diameter of clear zone obtained in n-hexane fraction is 27,3 mm (4000 ppm), 23,3 mm (2000 ppm), 22,3 mm (1000 ppm), 4,3 mm (500 ppm), 2 mm (250 ppm) and is 0 mm (125 ppm), while the fraction of ethyl acetate 24,6 mm (4000 ppm), 22 mm (2000 ppm), 19,6 mm (1000 ppm), 4,3 mm (500 ppm), 1,3 mm (250 ppm) and 0 mm (125 ppm). MIC of n-hexane fraction was 250 ppm with a diameter of 2 mm, and the ethyl acetate fraction was 250 ppm with a diameter of 1,3 mm. Conclusion:The conclusion of this research is the fraction of n-hexane and ethyl acetate fraction red seaweed Kappaphycus sp. has particulary inhibitory effect on bacterial growth staphylococcus aureusKeywords: Inhibition, Kappaphycus sp., antibacterial, Staphylococcus aureus.